Microstructure and mechanical properties of porous Si3N4/Invar joints brazed with Ag-Cu-Ti+Mo/Cu/Ag-Cu multi-layered composite filler. Issue 15 (15th October 2017) - Liu, J.Y.; Zhang, J.; Liu, C.F.; Wang, T.P.
Abstract: Ag-Cu-Ti/Cu/Ag-Cu multi-layered filler was successfully designed to braze porous Si3 N4 and Invar alloy. To further reduce the CTE mismatch between the porous Si3 N4 and brazing filler, Mo particles were introduced into Ag-Cu-Ti. The effects of the Mo addition on the microstructure and mechanical properties of the brazed joints were studied. The results showed that, the addition of Mo particles into Ag-Cu-Ti lowered the CTE mismatch and improved the joint strength to a certain degree. However, an excessive content was harmful. The Mo particles could absorb Ti at high temperature, causing Ti shortage in the reaction with the ceramic. When cooling down, the absorbed Ti was released. The released Ti could react with Cu to generate Cu-Ti phase. So, additional Ti was adopted in the brazing filler as a supplement. When the Ti content was 5 wt%, the reaction layer on the ceramic interface was too thin to transfer enough load. However, when it reached 15 wt%, the Cu interlayer dissolved completely and Fe-Ti and Ni-Ti phases appeared. The maximum joint shear strength (83 MPa) was obtained with 10 wt% Ti and 5 vol% Mo, which had exceeded 90% of the porous Si3 N4 and was 56% higher than the joint brazed without Mo particles.